INTEGRASI ARTIFICIAL INTELLIGENCE DALAM PENDIDIKAN ISLAM: TREN DAN ARAH PENELITIAN DALAM PERSPEKTIF BIBLIOMETRIK - Azwar, Azwar; Usman, Abur Hamdi; Abdullah, Mohd Farid Ravi (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2025)
This study aims to provide a comprehensive understanding of the development and research direction regarding the integration of Artificial Intelligence (AI) in Islamic education. It focuses on analyzing and mapping publication trends, researcher collaboration, institutional contributions, and dominant and underexplored topics. Using a bibliometric approach, the study draws on data from the Scopus database for the period 2015 to 2025. The findings reveal a significant increase in publication volume in recent years, with Indonesia emerging as the leading contributor, alongside institutions such as Universiti Kebangsaan Malaysia, International Islamic University Malaysia, and UIN Sunan Gunung Djati. Key contributors and the most influential works were identified, with Taufik M.’s article recognized as the most cited. Keyword mapping shows that research in this field centers on themes such as learning, models, approaches, and educational processes, with emerging trends including machine learning and AI-based evaluation. Several low-density topics, such as Islamic perspectives and deep understanding, indicate promising areas for future research. This study offers a valuable contribution to understanding the evolving scholarly landscape at the intersection of intelligent technology and Islamic educational values.   Abstrak Penelitian ini bertujuan untuk memberikan pemahaman komprehensif mengenai perkembangan dan arah riset terkait integrasi Artificial Intelligence (AI) dalam pendidikan Islam, melalui analisis dan pemetaan tren publikasi, kolaborasi peneliti, kontribusi institusi, serta topik-topik yang dominan dan belum banyak dieksplorasi. Penelitian ini dilakukan dengan pendekatan bibliometrik berdasarkan data dari basis data Scopus, mencakup periode tahun 2015 hingga 2025. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam jumlah publikasi selama beberapa tahun terakhir, dengan dominasi kontribusi dari Indonesia serta institusi seperti Universiti Kebangsaan Malaysia, International Islamic University Malaysia, dan UIN Sunan Gunung Djati. Penulis aktif dan karya paling berpengaruh juga diidentifikasi, dengan artikel Taufik M. sebagai publikasi paling banyak dikutip. Pemetaan kata kunci mengungkap bahwa fokus penelitian meliputi aspek-aspek seperti pembelajaran, model, pendekatan, dan proses pendidikan, serta tren baru seperti machine learning dan evaluasi berbasis AI. Beberapa topik dengan kepadatan rendah, seperti perspektif Islam dan pemahaman mendalam, menunjukkan potensi pengembangan riset di masa depan. Studi ini memberikan kontribusi penting dalam memahami dinamika keilmuan di persimpangan antara teknologi cerdas dan nilai-nilai pendidikan Islam.